Public agencies tweeting the COVID-19 pandemic: cross-country comparison of must have and forgotten communication topics - Tagliacozzo, Serena; Albrecht, Frederike; Ganapati, Nazife Emel (Frontiers in Communication, 2023)
Despite the importance of national-level public health agencies in times of a pandemic, there is limited comparative understanding of their must have and forgotten pandemic-related communication topics. To fill this gap in the literature, this article presents an analysis of COVID-related communication topics by national-level health agencies in Italy, Sweden, and the United States. The public health agencies included in the study are: the Italian National Institute of Health (Istituto Superiore di Sanità; ISS), the Public Health Agency of Sweden (Folkhälsomyndigheten), and the Center for Disease Control and Prevention (CDC) in the US. Based on these agencies’ Twitter posts (n=856) in the first three months of the pandemic, the article reveals a greater attention paid to disease prevention and disease trends and a limited attention paid to transmission and risk factors in all three countries. The study also highlights differences in terms of communication topics, especially in terms of these agencies’ emphasis on risk factors related to a person suffering from serious COVID-19-related health consequences (e.g., pre-conditions) and the chance of an individual to become infected with COVID-19 (e.g., being in crowded places).